Characterization of Multi-Walled Carbon Nanotube Film Sensor and Ethanol Gas-Sensing Properties - Dongzhi Zhang; Kai Wang; Bokai Xia (Universitas Ahmad Dahlan, 2013)
Multi-wall carbon nanotubes (MWNTs) film-based sensor on the substrate of printed circuit board (PCB) with inter digital electrodes (IDE) were fabricated using layer-by-layer self-assembly, and the electrical properties of MWNTs film sensor were investigated through establishing models involved with number of self-assembled layers and IDE finger gap, and also its ethanol gas-sensing properties with varying gas concentration are characterized at room temperature. Through comparing with the thermal evaporation method, the experiment results shown that the layer-by-layer self-assembled MWNTs film sensor have a faster response and more sensitive resistance change when exposed to ethanol gas, indicated a prospective application for ethanol gas detection with high performance and low-cost.